2021
DOI: 10.3389/fimmu.2020.615673
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Lupus B Cell Biology: PI3K, IFNγ, and Chromatin

Abstract: In the autoimmune disease Systemic Lupus Erythematosus (SLE), autoantibodies are formed that promote inflammation and tissue damage. There has been significant interest in understanding the B cell derangements involved in SLE pathogenesis. The past few years have been particularly fruitful in three domains: the role of PI3K signaling in loss of B cell tolerance, the role of IFNγ signaling in the development of autoimmunity, and the characterization of changes in chromatin accessibility in SLE B cells. The PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 125 publications
(188 reference statements)
0
11
0
Order By: Relevance
“…The activity of PI3K enzymes is mainly regulated by two lipid phosphatases, Phosphatase and Tensin Homolog deleted on Chromosome 10 (PTEN) and SH2‐containing inositol polyphosphate 5‐phosphatase (SHIP), which dephosphorylate PI(3,4,5)P 3 into PI(4,5)P 2 or PI(3,4)P 2 , respectively. Indeed, deletion of either PTEN or SHIP‐1 in B cells leads to activation of PI3K and dysregulated B cell development, maturation, and peripheral tolerance (reviewed in 70).…”
Section: The Pi3k Pathway: a Major Player In Central B Cell Selectionmentioning
confidence: 99%
“…The activity of PI3K enzymes is mainly regulated by two lipid phosphatases, Phosphatase and Tensin Homolog deleted on Chromosome 10 (PTEN) and SH2‐containing inositol polyphosphate 5‐phosphatase (SHIP), which dephosphorylate PI(3,4,5)P 3 into PI(4,5)P 2 or PI(3,4)P 2 , respectively. Indeed, deletion of either PTEN or SHIP‐1 in B cells leads to activation of PI3K and dysregulated B cell development, maturation, and peripheral tolerance (reviewed in 70).…”
Section: The Pi3k Pathway: a Major Player In Central B Cell Selectionmentioning
confidence: 99%
“…In our study, we presume that the mechanisms are related to the active compounds found in the mango's mistletoe leaf having anti-inflammatory, antiproliferative, and antioxidant properties [17]. The most of the flavonoid compounds found in the mango's mistletoe leaf interfere with metabolism, proliferation, survival, growth of B cells through the Akt/mTOR and Ras/ERK signaling pathways [22], [23], inhibit BAFF receptors on B cells [8] and obstruct the production of IFN-α, and BAFF by inhibition of pDCs [22], [24], [25]. In addition, a flavonoid also interferes with mDCs to activate T cells and IFN-ϒ, IL-17, and IL-21 production by T cells [22], [26].…”
Section: Cd28mentioning
confidence: 89%
“…IFNGR1 encodes the IFNγ receptor subunit 1, expressed on the surface of B cells. Elevated expression of IFNGR1 and subsequent IFNγ signaling activation promotes the loss of self-tolerance and production of autoantibodies in murine lupus models ( Bacalao and Satterthwaite, 2021 ). Our study suggests that the TNFAIP3 risk haplotype associated with SLE and other autoimmune diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%